Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 3 - Section 3.2 - The Product and Quotient Rules - 3.2 Exercises: 1

Answer

Both methods come out with the result: $$f'(x)=-8x^3+6x^2-2x+1$$

Work Step by Step

$$f(x)=(1+2x^2)(x-x^2)$$ 1) Using the Product Rule: $$f'(x)=(x-x^2)\frac{d}{dx}(1+2x^2)+(1+2x^2)\frac{d}{dx}(x-x^2)$$ $$f'(x)=(x-x^2)\times4x+(1+2x^2)\times(1-2x)$$ $$f'(x)=4x^2-4x^3+1-2x+2x^2-4x^3$$ $$f'(x)=-8x^3+6x^2-2x+1$$ 2) Performing the multiplication first: $$f(x)=x-x^2+2x^3-2x^4$$ So, $$f'(x)=\frac{d}{dx}(x-x^2+2x^3-2x^4)$$ $$f'(x)=-8x^3+6x^2-2x+1$$ The answers agree.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.